1976
DOI: 10.1172/jci108536
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of angiotensin II receptors in the rat adrenal cortex by dietary electrolytes.

Abstract: A B S T R A C T The binding affinity and concentration of specific angiotensin II receptor sites of rat adrenal cortical cells and homogenates were determined after 1 and 6 wk of altered sodium and potassium intake. Sodium deprivation caused marked increases in plasma renin, blood angiotensin II, and plasma aldosterone, and was accompanied by a significant increase (+ 74%) in the number of specific angiotensin II receptor sites per adrenal cortical cell. High potassium intake was followed by increased serum po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
1

Year Published

1981
1981
2008
2008

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(44 citation statements)
references
References 27 publications
4
39
1
Order By: Relevance
“…A progressive decrease in the number of ANG II receptors on hepatocytes was correlated with increasing adenosine 5'-diphosphate (ADP) ribosylation of M with pertussis toxin and loss of ANG II inhibition of cAMP production. 33 A similar relationship between opiate agonist receptor number and ADP-ribosylated Ni has been demonstrated with cultured Ng-108-15 cells. 41 The opposite was observed in the present study, in which enhanced binding was correlated with greater inhibition of cAMP production.…”
supporting
confidence: 54%
See 2 more Smart Citations
“…A progressive decrease in the number of ANG II receptors on hepatocytes was correlated with increasing adenosine 5'-diphosphate (ADP) ribosylation of M with pertussis toxin and loss of ANG II inhibition of cAMP production. 33 A similar relationship between opiate agonist receptor number and ADP-ribosylated Ni has been demonstrated with cultured Ng-108-15 cells. 41 The opposite was observed in the present study, in which enhanced binding was correlated with greater inhibition of cAMP production.…”
supporting
confidence: 54%
“…In hepatocytes, it has been demonstrated that the inhibitory guanine nucleotide-binding regulatory protein of adenylate cyclase (Ni) mediates the inhibitory effect of ANG II on adenylate cyclase. 33 In vivo, however, ANG II regulation of cAMP production mediated through Ni has not been previously shown. 33 Inhibition of cAMP production may be an important contributor to the amplification of the contractile response of the whole glomerulus beyond what can be explained by an increase in the number and affinity of ANG II binding sites.…”
Section: Ui-54mentioning
confidence: 97%
See 1 more Smart Citation
“…Nephrectomy or administration of angiotensin antagonists block the aldosterone secretory response in dogs subjected to dietary sodium deprivation (Davis, Ayers & Carpenter, 1961;Davis & Freeman, 1976;Stephens et al, 1977). Plasma aldosterone levels for any level of angiotensin II are higher during sodium depletion than during direct infusion of the octapeptide (Boyd et al, 1972); this may be due to an increase in the number of specific angiotensin II receptors on the adrenal glomerulosa cell (Douglas & Catt, 1976 (Haber et al, 1975;Samuels et al, 1976).…”
Section: Sodium Restrictionmentioning
confidence: 99%
“…The level of Ang II in plasma appears to regulate adrenal receptor number. Increasing the angiotensin level, either by sodium restriction or by continuous low-dose infusion by means of a minipump, 8 " 10 -20 ' 23 increases the number of adrenal receptors, while reducing the plasma level (sodiumloading or inhibiting angiotensin converting enzyme) 8 -' 02423 reduces angiotensin receptors. In our experiments, however, there were no significant differences between the PRA or plasma Ang II level of SHR and WKY on either high or low salt intake.…”
Section: Adrenal Ang II Receptor Regulationmentioning
confidence: 99%